2020
DOI: 10.3390/ma13112647
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cu2+ Ions on the Corrosion Resistance of AZ31 Magnesium Alloy with Microarc Oxidation

Abstract: The objectives of this study were to reduce the corrosion rate and increase the cytocompatibility of AZ31 Mg alloy. Two coatings were considered. One coating contained MgO (MAO/AZ31). The other coating contained Cu2+ (Cu/MAO/AZ31), and it was produced on the AZ31 Mg alloy via microarc oxidation (MAO). Coating characterization was conducted using a set of methods, including scanning electron microscopy, energy-dispersive spectrometry, X-ray photoelectron spectroscopy, and X-ray diffraction. Corrosion properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Li et al [43] showed that by adding rare earth elements, the corrosion resistance is improved by reducing the active area of the substrate surface. With the deepening of research, in recent years, strontium [44], gallic acid [45], and copper [46], which can enhance bone formation and antibacterial effects, have been added to electrolyte solutions.…”
Section: Effect Of Micro-arc Oxidation On Biocompatibilitymentioning
confidence: 99%
“…Li et al [43] showed that by adding rare earth elements, the corrosion resistance is improved by reducing the active area of the substrate surface. With the deepening of research, in recent years, strontium [44], gallic acid [45], and copper [46], which can enhance bone formation and antibacterial effects, have been added to electrolyte solutions.…”
Section: Effect Of Micro-arc Oxidation On Biocompatibilitymentioning
confidence: 99%
“…Presently, the corrosion of steels in seawater had been widely investigated all over the world [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and the influence of Cu 2+ on material corrosion is mainly focused on different materials in nonseawater environment, such as steel [21][22][23][24][25][26][27][28][29][30], aluminum alloy [31,32], 690 alloy [33], and copper alloy [34]. However, the works focused on the corrosion behavior of steels in seawater containing Cu 2+ and the influence of the Cu 2+ and copper oxides on the corrosion of the equipment in the secondary circuit system were little reported [35].…”
Section: Introductionmentioning
confidence: 99%